2021
DOI: 10.3171/2019.12.jns192506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative preoperative characteristics and postoperative outcomes at a private versus a safety-net hospital following endoscopic endonasal transsphenoidal resection of pituitary adenomas

Abstract: OBJECTIVESociodemographic disparities in health outcomes are well documented, but the effects of such disparities on preoperative presentation of pituitary adenomas (PA) and surgical outcomes following resection are not completely understood. In this study the authors sought to compare the preoperative clinical characteristics and postoperative outcomes in patients undergoing PA resection at a private hospital (PH) versus a safety-net hospital (SNH). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 31 publications
(31 reference statements)
0
16
2
Order By: Relevance
“…Prior studies have reported larger or more severe lesions at presentation for glioblastoma and pituitary adenoma patients at SNHs. 11 , 12 Higher brain tumor severity of illness at presentation may be the byproduct of barriers that limit access to care. 30 Because certain outcome differences did not persist following multivariate adjustment for severity metrics, such as increased mortality for glioma, greater presentation severity may partially account for observed outcome differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have reported larger or more severe lesions at presentation for glioblastoma and pituitary adenoma patients at SNHs. 11 , 12 Higher brain tumor severity of illness at presentation may be the byproduct of barriers that limit access to care. 30 Because certain outcome differences did not persist following multivariate adjustment for severity metrics, such as increased mortality for glioma, greater presentation severity may partially account for observed outcome differences.…”
Section: Discussionmentioning
confidence: 99%
“… 11 These resource constraints may also help explain the lower rates of tumor resection for glioma patients at SNHs (93.3%), compared to non-SNH patients (94.2%). Discrepancies in operative management may also be due to SNH patients being more likely to be ruled out as surgical candidates because of higher severity on presentation, 11 , 12 , 31 or lower trust in the healthcare system among marginalized patients due to past negative interactions and historical patterns of discrimination. 32 , 33 Alternatively, patients with brain tumors may have been transferred from a SNH to non-SNH for their surgery, reducing resection rates at SNHs; surgeons in non-SNHs may also have varying incentives, such as different compensation arrangements, that lead to higher rates of resection.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated at safety-net versus private hospitals have been more likely to be symptomatic from brain metastases, 25 to have delays to endovascular aneurysm embolization, 26 and to have increased rates of endocrinopathies after pituitary tumor surgery. 27 We were unable to account for the presence of safety-net hospitals, which appears to affect the quality of care delivered, and may have downstream effects on patient-physician communication. Along these lines, the current sample's breakdown of specialties differs from that of neurosurgeons throughout the country in the following numbers (our study vs national): functional (10% vs 2%), general practice (25% vs 51%), and spine (25% vs 12%), whereas similar proportions were seen in pediatrics (10% vs 8%) and tumor (16% vs 14%).…”
Section: Study Limitationsmentioning
confidence: 99%
“…There were 186 recorded operative times. Fibrous adenomas involved longer times (Table 3), which was maintained difference despite getting past the learning curve, with an increasing surgical time of 41 In the univariate analysis, brous adenomas showed a higher incidence of intraoperative CSF leak (OR 5.84, 95% CI 2.86-11.92, p = 0.001). After adjusting for tumor size, an OR of 5.24 (95% CI 2.49-11.02, p = 0.001) was obtained (Table 4).…”
Section: Intraoperative Variables and Consistencymentioning
confidence: 93%